Recent Advances on Natural Product Inspired Design and Synthesis of Medicinally Active Heterocycles - Vishwa Deepak Tripathi (Recent Advances on Natural Product Inspired Design and Synthesis of Medicinally Active Heterocycles, 2021)
Mother nature is the source of primary treatment of almost all the health ailments as well as inspiration for synthetic and medicinal chemists to explore the new chemical space. Natural molecules have shown their undoubted role in the area of medicine and chemotherapy. Gradually these natural molecules have inspired synthetic chemists to modify the natural product molecules in desired way to incorporate therapeutic potential in them. This fashion of tailoring the natural molecules in desired way arises the area of natural product inspired synthesis. The verified significance of natural molecules and natural product inspired synthesis motivated us to write this book containing a comprehensive compilation of natural product derived molecules with their detailed synthetic protocols and biological potential against different targets. The small synthetic molecules have been focused and they are categorized according to their biological activities and targets. We incorporated anticancer, antidiabetic, antifungal, antibacterial, antitubercular, antileishmanial and other activities. Various pharmacophoric nucleus selected from bioactive natural products and the pathway for their derivatization have been studied. The detailed synthetic protocol of the molecule is reported in an easy manner to correlate the structure and activity of molecule with the specific targets.